Motivasi Belajar dalam Perspektif Islam: Integrasi Niat, Keikhlasan, dan Pahala - Zakiyah, Afiefatuz; Mu’alimin Mu’alimin; Mukaffan Mukaffan (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze learning motivation from an Islamic perspective through the integration of spiritual values, including intention (niyyah), sincerity (ikhlas), and divine reward (pahala). Unlike modern motivation theories that emphasize psychological aspects, Islam views learning as an act of worship that carries spiritual merit and divine blessing. This research employs a qualitative approach using the literature review method, conducted through the collection of scientific articles from Google Scholar and Publish or Perish databases published between 2020 and 2025. Five relevant articles were selected for in-depth analysis. The results reveal that learning motivation in Islam is not only influenced by cognitive and external factors but also by spiritual drives rooted in pure intentions, sincerity in action, and belief in divine reward. The integration of these three elements forms a holistic model of learning motivation that combines intellectual, moral, and spiritual dimensions. Therefore, Islamic education should embed the values of intention, sincerity, and reward as the foundation for fostering meaningful and spiritually oriented learning motivation among students.